The impact of clinical social franchising on health services in low- and middle-income countries: a systematic review. - Naomi Beyeler; Anna York De La Cruz; Dominic Montagu (PLoS ONE)
Background The private sector plays a large role in health services delivery in low- and middle-income countries; yet significant gaps remain in the quality and accessibility of private sector services. Clinical social franchising, which applies the commercial franchising model to achieve social goals and improve health care, is increasingly used in developing countries to respond to these limitations. Despite the growth of this approach, limited evidence documents the effect of social franchising on improving health care quality and access. Objectives and methods We examined peer-reviewed and grey literature to evaluate the effect of social franchising on health care quality, equity, cost-effectiveness, and health outcomes. We included all studies of clinical social franchise programs located in low- and middle-income countries. We assessed study bias using the WHO-Johns Hopkins Rigour Scale and used narrative synthesis to evaluate the findings. Results Of 113 identified articles, 23 were included in this review; these evaluated a small sample of franchises globally and focused on reproductive health franchises. Results varied widely across outcomes and programs. Social franchising was positively associated with increased client volume and client satisfaction. The findings on health care utilization and health impact were mixed; some studies find that franchises significantly outperform other models of health care, while others show franchises are equivalent to or worse than other private or public clinics. In two areas, cost-effectiveness and equity, social franchises were generally found to have poorer outcomes. Conclusions Our review indicates that social franchising may strengthen some elements of private sector health care. However, gaps in the evidence remain. Additional research should include: further documentation of the effect of social franchising, evaluating the equity and cost-effectiveness of this intervention, and assessing the role of franchising within the context of the greater healthcare delivery system.